Data from: Linking genetic and ecological differentiation in an ungulate with a circumpolar distribution - Yannic, Glenn; Ortego, Joaquín; Pellissier, Loïc; Lecomte, Nicolas; Bernatchez, Louis; Côté, Steeve D. (Zenodo, 2017)
Genetic differentiation among populations may arise from the disruption of gene flow due to local adaptation to distinct environments and/or neutral accumulation of mutations and genetic drift resulted from geographical isolation. Quantifying the role of these processes in determining the genetic structure of natural populations remains challenging. Here, we analyze the relative contribution of isolation-by-resistance (IBR), isolation-by-environment (IBE), genetic drift and historical isolation in allopatry during Pleistocene glacial cycles on shaping patterns of genetic differentiation in caribou/reindeer populations (Rangifer tarandus) across the entire distribution range of the species. Our study integrates analyses at range-wide and regional scales to partial out the effects of historical and contemporary isolation mechanisms. At the circumpolar scale, our results indicate that genetic differentiation is predominantly explained by IBR and historical isolation. At a regional scale, we found that environmental dissimilarity and population size significantly explained the spatial distribution of genetic variation among populations belonging to the Euro-Beringian lineage within North America. In contrast, genetic differentiation among populations within the North American lineage was predominantly explained by IBR and population size, but not IBE. We also found discrepancies between genetic and ecotype designation across the Holarctic species distribution range. Overall, these results indicate that multiple isolating mechanisms have played roles in shaping the spatial distribution of genetic variation across the distribution range of a large mammal with high potential for gene flow. Considering multiple spatial scales and simultaneously testing a comprehensive suite of potential isolating mechanisms, our study contributes to understand the ecological and evolutionary processes underlying organism–landscape interactions. Ecography_ECOG-02995_DRYAD_2017 Table Dryad 1. Sampling sites, number of individuals ...